Interactive Mixed Reality Museum for Ulos Batak Cultural Heritage Preservation and Global Recognition - Halim, Jasmine Meilani; Lubis, Dinda Pebriani; Hasibuan, Aziz Parham Ramadhan; Syardhi, Rizfan Dio; Ningsih, Ranti Widya; Alda, Tania (Talenta Publisher, 2024)
Indonesia, with its abundant cultural riches, faces challenges in preserving the traditional Batak cloth, Ulos, which is now threatened by globalization and foreign cultural claims. Ulos, which has been designated as Indonesia's Intangible Cultural Heritage (WBTb) since October 17 2014, has not yet received international recognition from UNESCO as part of the Intangible Cultural Heritage (ICH) list. This recognition is very important to increase global awareness about Ulos and the need for its preservation. Considering these challenges, this research proposes the creation of